2018
DOI: 10.1590/0037-8682-0377-2017
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis in pregnancy, congenital syphilis, and factors associated with mother-to-child transmission in Itapeva, São Paulo, 2010 to 2014.

Abstract: Syphilis in pregnancy, congenital syphilis, and factors associated with mother-to-child transmission in Itapeva, São PauloAbstract Introduction: This study describes cases of syphilis in pregnancy (SiP) and congenital syphilis (CS) and identifies factors associated with mother-to-child transmission in patients in Itapeva from January 1, 2010 to December 31, 2014. Methods: Using SiP and CS notification forms and medical records, a cross-sectional study involving 149 pregnant women was conducted. Results: Annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
3
4
0
Order By: Relevance
“…However, it worth noting that many records contained missing race/ethnicity classi cation data in P1, which can be considered as a bias in the interpretation of our results. Indeed, the data presented herein corroborate other studies that identi ed a signi cant correlation between these sociodemographic characteristics and SiP [15,[21][22][23][24][25][26][27]29,30,[32][33][34][35][36][37][38]. We suggest that distinct strategies are required to reach more vulnerable populations and to minimize inequalities that enable greater access to health services.…”
Section: Discussionsupporting
confidence: 88%
“…However, it worth noting that many records contained missing race/ethnicity classi cation data in P1, which can be considered as a bias in the interpretation of our results. Indeed, the data presented herein corroborate other studies that identi ed a signi cant correlation between these sociodemographic characteristics and SiP [15,[21][22][23][24][25][26][27]29,30,[32][33][34][35][36][37][38]. We suggest that distinct strategies are required to reach more vulnerable populations and to minimize inequalities that enable greater access to health services.…”
Section: Discussionsupporting
confidence: 88%
“…However, it worth noting that many records contained missing race/ethnicity classi cation data in P1, which can be considered as a bias in the interpretation of our results. Indeed, the data presented herein corroborate other studies that identi ed a signi cant correlation between these sociodemographic characteristics and SiP [15,[21][22][23][24][25][26][27]29,30,[32][33][34][35][36][37][38]. We suggest that distinct strategies are required to reach more vulnerable populations and to minimize inequalities that enable greater access to health services.…”
Section: Discussionsupporting
confidence: 89%
“…One of the main purposes of prenatal care is to assist women in a quali ed and humanized way beginning in the early stages of pregnancy, adopting early screening procedures coupled with timely interventions [28]. Early diagnosis and treatment of SiP, ideally before the 20 th week of pregnancy, can reduce CS-related cases, such as miscarriages, stillbirths, and infant deaths [29]. It is therefore important that all pregnant women be tested at the rst prenatal visit scheduled in the rst trimester of pregnancy, with repeat testing performed at around 28 weeks and in the beginning of the third trimester in order to promptly implement appropriate therapy if necessary [30].…”
Section: Discussionmentioning
confidence: 99%
“…This was quite similar to a previous study in Thailand, which reported the median (IQR) maternal age of 21 (18–32) years among 69 pregnant women [ 23 ], but was lower than the age of mothers with syphilis from other studies. A study from China reported 155 mothers with syphilis, of whom none were under 20 years old [ 10 ], as well as a report of 149 mothers with syphilis from Brazil, whose median age was 24 years old [ 7 ]. Despite the efforts from national campaigns to eliminate congenital syphilis in Thailand and the high proportion of mothers that attended ANC in our study, mothers of 48.4% of neonates (61/126) had no syphilis treatment or inadequate treatment, which was comparable to 41% among 69 pregnant women reported in other studies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the number of reported congenital syphilis cases has increased from 8.4 cases per 100,00 live births in 2012 to 33.1 cases per 100,00 live births in 2018, reaching a 20-year high [ 6 ]. A cross-sectional study from a city in Brazil found that the incidence of congenital syphilis increased from 121 to 223 per 100,000 live births in 2011 and 2014, respectively [ 7 ]. Reports on risk factors associated with congenital syphilis from the United States and other countries included lack of prenatal care, lack of antenatal screening, delayed diagnosis of syphilis in pregnant women, untreated or inadequately treated pregnant women, and low socioeconomic status [ 7 , 8 , 9 , 10 ].…”
mentioning
confidence: 99%